Clinicohistopathological study and expression of CK7 and CK20 in mucinous tumors of gastrointestinal tract and ovary - Killana, Santhosh Rupa; Uma, Prasad; Lakshmi, Atla Bhagya; Laxmi Trivedi, Uttapalla; Hari Chandan Kumar, Juthuga; Arjuna, Gera (International Journal of Research in Medical Sciences, 2022)
Background: Mucinous ovarian tumors differ from other types of epithelial ovarian cancers in their clinical behaviour and the need for innovative treatment approaches to achieve improved patient outcomes. Immunohistochemistry plays an important role in diagnosis and differentiates primary and secondary mucinous tumors. To know the distribution and expression of CK7 and CK20 in mucinous tumors of ovary and gastrointestinal tract. Methods: Ninety eight cases of mucinous tumors of ovary and gastrointestinal tract were analysed as per standard protocol out of which malignant mucinous tumors constituted forty five cases. All 45 cases of mucinous carcinoma of ovary and gastrointestinal tract were subjected to IHC CK7 and CK20. The results were analysed. Results: Total mucinous tumors of ovary were 64 cases and total mucinous tumors of gastrointestinal tract were 34 cases. Predominant expression in primary mucinous carcinoma of ovary was CK7 positive and CK20 positive, in metastatic mucinous ovarian carcinoma of gastric origin was CK7 positive and CK20 positive and from colorectal origin was CK7 negative and CK20 positive. Signet ring cell carcinoma of stomach showed CK7 diffuse positivity with focal CK20 positivity. Colorectal mucinous carcinoma was CK7 negative and CK20 positive. The expression varied with the stage of the disease. Conclusions: CK7 and CK20 plays an important role in differentiating primary mucinous carcinoma of ovary from metastatic ovarian carcinoma arising from lower gastrointestinal tract.CK7 and CK 20 expression is variable with stage of disease hence should be interpreted in the background of histopathology.